Introduction - Katz, L. F. (Quarterly Journal of Economics, 1992)
Introduction Get access Lawrence F. Katz Lawrence F. Katz Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 107, Issue 1, February 1992, Page i, https://doi.org/10.2307/2118321 Published: 01 February 1992